Validez de instrumento para medir el aprendizaje creativo (2016)
The article presents the validity and reliability of CREA instrument, its objective is to evaluate the creative learning students pursuing undergraduate academic programs in the city of C´ucuta, Colombia. Follows a descriptive study design validation through multidimensional scaling factor analysis, construct validity, and facial. The study population were students of undergraduate engineering, management and agricultural sciences aged between 18 and 25 years in the city of Cucuta, Colombia, the sample constituted by 595 students. A scale of 35 items was obtained. Factor analysis showed dimensions of teaching practice-oriented leadership, creative thinking, emotional fulfillment, independence, creative attitude, productivity, leadership skills, motivation; Internal consistency was adequate (Cronbach’s alpha 0.72 to 0.95), intraclass correlation coefficient of 0.967 overall (95 % CI, 0933- 0984), differences in average sum of items -1.3 (SD 8.5) and Kappa indices greater than 0.9, it shows high agreement among experts. It is concluded that CREA is a valid and reliable for the context Cucuta, Colombia instrument.